PENGARUH TERAPI MUSIK TERHADAP KECEMASAN PRA ANESTESI DI RUANG OPERASI: The Effect of Music Therapy on Anxiety in Pre-Anesthesia in the Operating Room - Astri Yunita; Arie Jefry Ka’arayeno; Santy Irene Putri; Liya Ni’matul Maula; Berna Detha Meilyana (Forind Press, 2023)
Spinal anesthesia is an action taken before surgery so that patients feel safe and comfortable during surgery and avoid postoperative pain. The purpose of the study was to analyze the effect of music therapy on pre-anesthesia anxiety in the operating room. The research design is a quasi-experiment with a pre and post approach. The population was all patients who underwent surgery with spinal anesthesia. Samples taken in this study patients who underwent surgery with spinal anesthesia amounted to 30 samples. The independent variable is music therapy. The dependent variable is anxiety. The analysis used is univariate and bivariate analysis. The results of statistical test analysis using paired t test after given music therapy showed that p<0.001 (p<0.05), so it can be concluded that there is a difference in the effect of health education before and after music therapy on anxiety in pre-anesthesia. Music therapy can have a calming effect on respondents, can reduce anxiety, make feelings relaxed, relaxed, and can stabilize emotionally.